Surgical Treatment in Active Infective Endocarditis: Results of a Four-Year Experience. (18th May 2011) - Rostagno, Carlo; Carone, Enrico; Rossi, Alessandra; Gensini, Gian Franco; Stefano, Pier Luigi
Abstract : Background . Aim of present investigation was to analyze survival and recurrence rate in patients with active endocarditis referred to our centre for surgical treatment. Methods . 80 consecutive patients with active infective endocarditis (52 males, 28 females, mean age 59.2 years) were referred to our institution for surgical treatment. 78 patients underwent surgery, and 2 patients died before intervention. Results . Fifty patients had native valve endocarditis, 30 prosthetic valve involvement. Hospital mortality has been 10.2%. Three discharged patients (4.9%) died at an average 18-month followup. Endocarditis recurred in 4 (2 being S. aureus prosthetic tricuspid endocarditis in drug addicts). All patients who underwent valve repair or homograft implant were alive and free of recurrence. Conclusions . Our results suggest that with proper surgical treatment patients with active endocarditis discharged alive from hospital have a survival >90% at 18 months with a low recurrence rate.